Pengembangan UMKM Melalui Digital Marketing di Desa Gambiran - Aufia Aisa; Purbowo Purbowo; Siti Sulaikho; Mochammad Ilham Ramadhani; Fahim Mubarok; Putri Lestari; Mariyanti Mariyanti; Rizka Annisa (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Efforts by Micro, Small and Medium Enterprises to face global competition by implementing digital marketing in business enterprises, both small, medium and large, so that the level of competitiveness of business people can increase. In this regard, the use of digital marketing is not widely recognized by business people, especially MSMEs in Gambiran Village, most of whom still apply marketing using offline methods. The aim of this service is to help implement digital marketing in marketing, thereby encouraging producers' interest in marketing development. The parties involved in this activity are MSME actors in Gambiran Village. The approach method in this service activity uses CBR (Community Based Research). The implementation method uses a face-to-face seminar method at the Gambiran Village Sports Hall with around 10 participants. The results of this activity can provide awareness and help MSMEs to implement digital marketing in marketing.